Implementasi Coretax dalam Registrasi Nomor Pokok Wajib Pajak (NPWP) Orang Pribadi di KPP Pratama Karawang - Syifa Nida Zahra; Angga Sanita Putra; Arif Rakhman; Nesti Hapsari; Kholida Atiyatul Maula (AKUNTANSI 45, 2026)
The digitalization of tax administration through the Coretax system is expected to improve the efficiency of tax services. However, in its implementation, there are still various obstacles faced, so the effectiveness of this digital system’s implementation has not reached optimal levels. This review aims to describe the implementation of Coretax, identify the obstacles that occurred, analyze the solutions applied by tax volunteers, and provide recommendations to improve the system’s effectiveness. The method used is qualitative descriptive. Data collection was conducted through triangulation by combining observation, documentation, and interviews with 14 tax volunteers, according to Sugiyono’s theory. Data analysis using Miles & Huberman’s method involves three stages, namely data reduction, data display, and conclusion drawing, carried out interactively and continuously until completion, resulting in data saturation. The review results show that the obstacles encountered are systemic and interconnected, including technical barriers, population data validation, administrative issues, infrastructure, and regulations. The solutions provided by volunteers show a consistent pattern, such as using personal hotspots, bringing personal devices, coordinating with Tax Office staff, directing taxpayers to the Civil Registration Office, and providing education in easily understood language. This review concludes that the success of Coretax implementation is influenced not only by system design but also by sustainable maintenance, inter-agency integration, infrastructure readiness, and effective regulation socialization.